Judicial Application of Actus Reus and Mens Rea In Village Fund Corruption Cases - Aprilia Khoirun Nisa; Ali Maskur (Jurnal Ius Constituendum, 2026)
Reus and Mens Rea In Village Fund Corruption Cases   Aprilia Khoirun Nisa, Ali Maskur  Faculty of Sharia and Law, Walisongo State Islamic University, Semarang, Indonesia apriliakhoirunnisa22@gmail.com   Abstract   This study examines the judicial application of actus reus and mens rea in village fund corruption cases, with a specific focus on Decision Number 2/Pid.Sus-TPK/2024/PN Smg involving a village head in Blora Regency. The persistence of corruption at the village governance level highlights the need for doctrinal consistency between judicial reasoning and classical principles of criminal liability. Using a normative juridical method with statutory, case, and conceptual approaches, this research analyzes how the court established the outward unlawful conduct (actus reus) through proven abuse of authority, manipulation of village financial administration, and resulting state financial losses, as well as how it inferred the inward culpable intent (mens rea) from deliberate and systematic misuse of public funds. The findings demonstrate that the judge’s reasoning substantially aligns with Moeljatno’s theory, which emphasizes the unity between unlawful acts and moral blameworthiness as the foundation of criminal responsibility. The judgment also reflects formal compliance with Supreme Court Regulation Number 1 of 2020 on corruption sentencing guidelines, although its emphasis on nominal financial loss raises normative tension with the primacy of moral culpability in classical criminal law. The novelty of this study lies in its integrated doctrinal assessment that simultaneously evaluates actus reus, mens rea, causality, and sentencing considerations, thereby reaffirming the continued relevance of classical criminal law theory in contemporary corruption adjudication involving village funds.